Clinical-pathomorphological characteristic of stomach ulcer with different sizes of ulcerous defects - R. A. Abdulkhakov (Бюллетень сибирской медицины, 2005)
It was studied 58 patients with medium size ulcer and 182 with big size ulcers in order to compare activity of stomach ulcer and duodenum disease of patients with medium and big ulcerous defects and discover its peculiarities depending on sizes of ulcers. It was discovered that big size ulcers occur more frequently among the age between 40–49 (32.42%) and more often in stomach than in duodenum. High secretory function of stomach is discovered among most of patients.